Landscape of paediatric endocrine clinical practice in Italy: results from a survey of the Italian Society for Paediatric Endocrinology and Diabetology (ISPED) - Maria Elisabeth Street; Anna Di Sessa; Andrea Esposito; Anastasia Ibba; Giorgia Pepe; Riccardo Bonfanti; Felice Citriniti; Giuseppe D’Annunzio; Maria Rosaria Licenziati; Malgorzata Wasniewska; Valentino Cherubini; Mariacarolina Salerno (Italian Journal of Pediatrics)
Abstract Background Pediatric endocrinology has developed enormously over the last 30 years. Many conditions followed-up are rare and/or chronic complex diseases requiring a high level of expertise. Therefore, defining pediatric endocrinology workforce has become crucial. We aimed to provide an overview of the landscape of the Italian Pediatric Endocrinology centers. Methods A national electronic survey on clinical endocrine practice among the Italian Society for Pediatric Endocrinology and Diabetes (ISPED) centers was carried out. The full time equivalent (FTE) was used to assess the time dedicated by healthcare providers (HCPs) to pediatric endocrinology and calculate the needs. Results Ninety-one centers completed the electronic survey. Forty-four/91 centers had incorporated a pediatric diabetology service, while the remaining had an independent center. Among HCPs, 271 were pediatric endocrinologists (94 with a temporary, and 265 with a permanent contract). In 14/91 centers, adult endocrinologists were part of the medical staff. In 45/91 centers clinical activity was carried out five days a week. A mean FTE of 0.56 for medical doctors, 0.49 for nurses, 0.31 for dietitians, and 0.13 for psychologists was reported. An average of 110 patients with rare diseases was followed per centre per year. Based on the ISPAD international criteria for the FTE required for the care of diabetic youths we considered rare diseases as a reference instead of diabetes, without considering any other consultations, and this showed a shortage of 80% of required pediatric endocrinologists, 89% of needed nurses, 93% of required dietitians, and 94% of required psychologists. Moreover, approximately 20 pediatric endocrinologists were expected to retire within the following two years. Overall, a mean of 1148 consultations/year per centre was reported for each medical FTE (a mean of 367 first consultations, and 786 follow-ups). Education and training for growth hormone and other specific treatments were provided by a variety of HCPs, mainly by medical doctors (22/91 centers). Conclusions At present pediatric endocrinology shows a significant burden of activity with a severe shortage of personnel. This should be addressed by policy makers in order to develop strategic programs to ensure optimal care. Recognizing pediatric endocrinology as a subspecialty and offering appropriate training programs would represent a significant step further.